Palmar erythema [Palmar eritem] - (:unkn) unknown (My University, 2007)
Palmar erythema is a clinical sign presenting with symetrical erythema of both palms. It is usually asymptomatic and may seldom be seen in healthy individuals. Systemic diseases, drugs, chemicals, neoplasms and infections may play a role in the etiology. We prepared this review on palmar erythema, an issue which we believe is usually clinically underestimated, in order to view associated pathologies, to describe different forms and to be a guide in patient assessment.
Keywords: Drug eruption; Infection; Palmar erythema